Viola pluviae sp. nov. (Violaceae), a member of subsect. Stolonosae in the Pacific Northwest region of North America. (26th September 2018) - Blaxland, Kim; Ballard, Harvey E.; Marcussen, Thomas
Abstract : As hirtherto circumscribed, the allo‐octoploid Viola palustris L. exists in three distinct races in North America. The race occurring in the Pacific Northwest of North America has previously been shown to have originated by polyploidy from a different set of ancestral tetraploids than the nominal, Amphi‐Atlantic race. These two races differ also in a number of morphological characters, which has been a historical source of confusion. We here propose a new name for the western plants, V . pluviae Marcussen, H.E. Ballard & Blaxland, and typify it with a specimen collected near Mt Rainier (USA, Washington) with known chromosome number. Distribution, phylogenetic history and taxonomy are discussed and an updated morphological key to the Pacific Northwestern species of Viola is presented.